(untitled) (Fiep Bulletin - online, 2011)
Between 2 to 7 years can be observed in the motor development of children’s acquisition of the fundamental patterns of movement, and for a good quality standards of the child must be as close as possible to mature stage. The objective of this research is to identify the maturational stage of the movement patterns of the guided walk, the horizontal jump and the act of getting children between 4 and 6 years of activity taekwondo practitioners. This is a descriptive research that has sampled 27 children of 4years, 41 5 and 32 6 years practicing taekwondo members of 12 elementary schools and 6 colleges in the cities of Belo Horizonte and Contagem / MG. An evaluation of the maturational patterns of movement (walking, jumping and receive) in accordance with Gallahue and Ozum (2005). Data processing was done using descriptive statistics. Observed as a result, except for group of 4 year olds in the movement patterns of jumping and receivables presented in the initial stage, all other children in this study are in the maturity stage on the age or is in a upper stage.